ALK inhibitors for non-small cell lung cancer: A systematic review and network meta-analysis. - Jesse Elliott; Zemin Bai; Shu-Ching Hsieh; Shannon E Kelly; Li Chen; Becky Skidmore; Said Yousef; Carine Zheng; David J Stewart; George A Wells (PLoS ONE)
Background We sought to assess the relative effects of individual anaplastic lymphoma kinase (ALK) inhibitors for the treatment of non-small cell lung cancer (NSCLC). Methods We searched MEDLINE, Embase, Cochrane CENTRAL, and grey literature (July 23, 2019) for randomized controlled trials (RCTs) that included participants with ALK- or ROS1-positive NSCLC who received any ALK inhibitor compared with placebo, another ALK inhibitor, or the same ALK inhibitor at a different dose. The primary outcome was treatment-related death. Secondary outcomes were overall survival (OS), progression-free survival (PFS), and serious adverse events. Data were pooled via meta-analysis and network meta-analysis, and risk of bias was assessed. PROSPERO: CRD42017077046. Results Thirteen RCTs reporting outcomes of interest among participants with ALK-positive NSCLC were identified. Treatment-related deaths were rare, with 10 deaths attributed to crizotinib (risk difference v. chemotherapy: 0.49, 95% credible interval [CrI] -0.16 to 1.46; odds ratio 2.58 (0.76-11.37). All ALK inhibitors improved PSF relative to chemotherapy (hazard ratio [95% CrI]: crizotinib 0.46 [0.39-0.54]; ceritinib 0.52 [0.42-0.64]; alectinib 300 BID 0.16 [0.08-0.33]; alectinib 600 BID 0.23 [0.17-0.30]; brigatinib 0.23 [0.15-0.35]), while alectinib and brigatinib improved PFS over crizotinib and ceritinib (alectinib v. crizotinib 0.34 [0.17-0.70]; alectinib v. ceritinib 0.30 [0.14-0.64]; brigatinib v. crizotinib 0.49 [0.33-0.73]; brigatinib v. ceritinib 0.43 [0.27-0.70]). OS was improved with alectinib compared with chemotherapy (HR 0.57 [95% CrI 0.39-0.83]) and crizotinib (0.68 [0.48-0.96]). Use of crizotinib (odds ratio 2.08 [95% CrI 1.56-2.79]) and alectinib (1.60 [1.00-2.58]) but not ceritinib (1.25 [0.90-1.74), increased the risk of serious adverse events compared with chemotherapy. Results were generally consistent among treatment-experienced or naïve participants. Conclusion(s) Treatment-related deaths were infrequent among ALK-positive NSCLC. PFS may be improved by alectinib and brigatinib relative to other ALK inhibitors; however, the assessment of OS is likely confounded by treatment crossover and should be interpreted with caution.